Review of brain and brain cancer treatment - R.Srinivasan; L. Manoj; M.Kalyani; K.Jyothi; G.Ganga Bhavani; V.Govardhani (International Journal of Pharma and Bio Sciences, 2011)
The brain and spinal column make up the central nervous system (CNS), where all vital functions of the body are controlled. When tumors arise in the central nervous system, they are especially problematic because a persons thought processes and movements can be affected. These tumors can also be difficult to treat because the tissues surrounding a tumor that may be affected by surgery or radiation may play a vital role in functioning. There are two broad types of cancers occurring within this system. Primary tumors originate in the central nervous system, whereas secondary tumors migrate from cancers located elsewhere in the body, such as breast cancers. Secondary, or metastatic, brain tumors, are more common than primary brain cancers. This section focuses on primary stages on brain cancer.